NON-VERBAL BEHAVIOR AS AN ELEMENT OF COMMUNICATIVE COMPETENCE OF A FUTURE TEACHER OF ECONOMICS - Shepelenko Т.Л. (Pedagogy of Higher and Secondary Education, 2022)
The paper discloses the essence of nonverbal behavior and ways of its formation in the learning process of higher education.